WOMEN’S PARTICIPATION IN ABACA FARMING: A CASE IN BAYBAY LEYTE, PHILIPPINES - Mary Cris F. PLEÑOS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study examines the involvement of women in abaca farming activity at various phases. Selection of the respondents was done by simple random sampling, and the data were collected using survey questionnaire. The data were analyzed using descriptive analysis, which included frequency counts, percentages and mean. According to the findings, women participated in all aspects of abaca farming, however men are more heavily involved than women because it is a labor-intensive livelihood. Women were commonly involved in abaca-related decision-making, as well as in the sale of abaca fiber and the management of abaca farm earnings.